Targeting Inflammation in Chronic Kidney Disease: Pathophysiological Insights and Emerging Therapeutic Strategies - Aris Tsalouchos; Pietro Claudio Dattolo (Journal of Clinical Medicine, 2026)
Chronic kidney disease (CKD) is sustained by a network of sterile inflammation, oxidative and metabolic stress, uremic toxin retention, gut barrier dysfunction, and maladaptive immune activation. These processes contribute to kidney fibrosis, cardiovascular injury, wasting, and excess mortality, but inflammatory biomarkers do not by themselves establish therapeutic causality. This narrative review integrates mechanistic and therapeutic evidence using an explicit three-layer translational hierarchy. Renin–angiotensin system inhibitors, sodium–glucose cotransporter-2 inhibitors, finerenone, and glucagon-like peptide-1 receptor agonists improve cardiorenal outcomes and have plausible anti-inflammatory actions, although inflammatory mediation remains unproven. Interleukin-1 blockade provides cardiovascular proof of principle and small dialysis feasibility data. Interleukin-6 ligand inhibition produces marked human target engagement; however, headline results from the completed phase 3 ZEUS trial showed no reduction in three-point major adverse cardiovascular events with ziltivekimab despite biomarker suppression, while serious infections were more frequent. POSIBIL6ESKD continues to test clazakizumab in inflamed dialysis patients. Direct NLRP3 inhibition has entered early human CKD development, whereas senescence-directed and microbiota-based approaches remain less mature. Future progress requires inflammatory endotyping, repeated biomarker assessment, mechanistically aligned outcomes, and rigorous infection surveillance. ZEUS underscores that pathway suppression must deliver clinical benefit beyond contemporary standard therapy.